Managing technological innovation : competitive advantage from change - Betz, Frederick , 1937- (Hoboken, New Jersey : John Wiley & Sons, 2011)
"Frederick Betz is one of the original creators of "technology management" and was Director of the TM program at the NSF. His first book on Management of Technology published by Prentice Hall 16 years ago has been acknowledged as setting the foundation for the subject. Betz further helped crystalize the field of technology management and the management of innovation with the first two editions of Managing Technological Innovation. With this third edition he will bring the subject inline with current business strategy. This edition will present information in a newer organized format that aligns more closely with how the topics are presented and discussed in the classroom. Planned for inclusion will be a greater discussion of how science and technology interact with the global economy"
1. Technological innovation -- 2. Innovation and economy -- 3. Innovation and national systems -- 4. Innovation research -- 5. Innovation and corporate R&D -- 6. Innovation and markets -- 7. Innovation and product development -- 8. Innovation and strategy -- 9. Integrating technology and business strategy -- 10. Inventing technology -- 11. Technology systems -- 12. Product systems -- 13. Service systems -- 14. Biotechnology systems -- 15. Ethics and technology -- 16. Innovation practice
Includes bibliographical references (p. 339-348) and index
Keywords: Research, Industrial -- Management; Technological innovation -- Management